1975
DOI: 10.1128/aac.7.5.582
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1-β- d -Ribofuranosyl-1,2,4-Triazole-3-carboxamide Against Influenza Virus Infections in Mice

Abstract: 1-β- d -Ribofuranosyl-1,2,4-triazole-3-carboxamide (ribavirin) was effective against strains of influenza virus types A and F, whereas amantadine hydrochloride was effective only against strains of influenza virus type A. Dose-related protective effects against lethal influenza infections in mice were obtained with single oral doses of 25 to 400 mg of ribavirin per kg administered at the time of virus inoculation or up to 24 h thereafter. Therapeutic indexes (maximum tolerated dose/medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The doses of ribavirin selected either were known to be effective in vivo (as in the influenza virus model [4]) or approached the limiting toxicity for the particular species. With N10169, the poor solubility of the compound was a factor which limited its utility to 300 mg/kg.…”
Section: Materials Ani) Methodsmentioning
confidence: 99%
“…The doses of ribavirin selected either were known to be effective in vivo (as in the influenza virus model [4]) or approached the limiting toxicity for the particular species. With N10169, the poor solubility of the compound was a factor which limited its utility to 300 mg/kg.…”
Section: Materials Ani) Methodsmentioning
confidence: 99%
“…It has been suggested that this inhibition would be lethal to replicating virus but would have little effect on resting cells. Some evidence for this is provided by cytotoxicity studies on uninfected cells, wherein it has been reported that even at high concentrations (1,000 ,ug/ml), little visible cytotoxicity in terms of degenerating cells or destruction of cell monolayers was seen, although the rate of cell proliferation was effectively reduced (2,6).…”
mentioning
confidence: 99%
“…Ribavirin (1-fl-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) is a synthetic nucleoside which has both in vitro (2,6,10) and in vivo (1,3,5,7) antiviral activity against a variety of ribonucleic acid and deoxyribonucleic acid viruses. The compound acts by interfering with guanidine monophosphate formation and subsequent nucleic acid synthesis (9).…”
mentioning
confidence: 99%
“…Recently, ribavirin (1-3-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) was found to be effective for the treatment of type A influenza virus infections in mice (1,(3)(4)(5). These experiments indicated that small-particle aerosols (mass median diameter, 1.4 gm) of ribavirin were more effective in reducing mortality, lesions in the lung, and virus concentrations in the lungs than approximately equivalent doses of drug given intraperitoneally (i.p.)…”
mentioning
confidence: 99%
“…A virus control group received no treatment. The degree of gross pathology in the lungs (lung lesion score) was evaluated in three mice on day 4 and in five mice on day 7 by 1 Present address: Plum Island Animal Disease Center, P.O. Box 848, Greenport, NY 11944. methods that have been described previously (4).…”
mentioning
confidence: 99%